(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Identifying the health care needs of first-year students at Vietnam National University, Hanoi (VNU), academic year 2021-2022. Subject and method: Cross-sectional descriptive study on 1,829 first-year students of Vietnam National University, Hanoi admitted and had an entrance health check at VNU Hospital. Results: 73.81% of students have a need to use health consulting services. The content that students want to be consulted the most is psychological counseling, mental health (72.59%), nutritional counseling (64.89%), and accident and injury counseling is 52.59%. 50.89% of students want to set up a counseling facility at their school and 47.19% of students want to set up a counseling facility at VNU Hospital. The need for training in first aid accounts for 65.12%. The main first aid content that students want to be trained in is: first aid for cardiac arrest 64.07%; first aid for fainting 58.86%; first aid for skin lacerations 55.33%; first aid for fractures 44.92%. Students mainly choose the training method 63.39%; regular teaching 30.39%.. Conclusion: The need for health care and first aid consultation among students is very large and they want to be consulted right at their school as well as at VNU Hospital.